Odpowiedź :
x + y = 66
0,8x + 0,75y = 51 \\*10
x+y=66 => x=66-y
8x+7,5y=510
8*66-8y+7,5y=510
528-0,5y=510
0,5y=18
y=36
x=66-36=30
0,8x + 0,75y = 51 \\*10
x+y=66 => x=66-y
8x+7,5y=510
8*66-8y+7,5y=510
528-0,5y=510
0,5y=18
y=36
x=66-36=30
x + y = 66
0,8x + 0,75y = 51
x=66-y
0,8(66-y) + 0,75y = 51
x=66-y
52,8-0,8y+0,75y=51
x=66-y
-0,05y=51-52,8
x=66-y
-0,05y=-1,8 /*(-1)
x=66-y
0,05y=1,8
x=66-y
y=36
x=66-36
y=36
x=30
y=36
0,8x + 0,75y = 51
x=66-y
0,8(66-y) + 0,75y = 51
x=66-y
52,8-0,8y+0,75y=51
x=66-y
-0,05y=51-52,8
x=66-y
-0,05y=-1,8 /*(-1)
x=66-y
0,05y=1,8
x=66-y
y=36
x=66-36
y=36
x=30
y=36
x+y=66
0,8x + 0,75y =51 / x10
x+y=66 /-y
8x+7,5y =510
x=66-y
8x+7,5y=510
x=66-y
8(66-y) +7,5y =510
528-8y +7,5y = 510 /-528
x=66-y
x=66-y
-0,5y = -18 / x(-2)
x=66-y
y=36
x=66-36
y=36
x=30
y=36
0,8x + 0,75y =51 / x10
x+y=66 /-y
8x+7,5y =510
x=66-y
8x+7,5y=510
x=66-y
8(66-y) +7,5y =510
528-8y +7,5y = 510 /-528
x=66-y
x=66-y
-0,5y = -18 / x(-2)
x=66-y
y=36
x=66-36
y=36
x=30
y=36